Sensitivity of tuberous roots crops to salinity in a protected environment - Polo, Gabriel Furlan; Freitas, Murillo Ribeiro; Cunha, Pamela Stephany Jennings; Vendruscolo, Eduardo Pradi; Seron, Cássio de Castro; Martins, Murilo Battistuzzi; Zoz, Tiago (Revista de Ciências Agroveterinárias, 2022)
Soil salinity has been a limiting barrier for the production of vegetables in protected environments. Thus, the understanding of the sensitivity of species to this stress factor must be explored, seeking better growing conditions. Under the hypothesis that beet and radish crops are sensitive to variations in soil salinity, even at low levels, the objective of this work was to evaluate the development and productivity of these two species in soils with different salinities in a protected environment. The experimental design was completely randomized and treatments were formed by the soil salinity levels, obtained with the application of saline solution (NaCl in water), considering the soil electrical conductivity of 0.36 dS m-1 as low salinity, of 1.05 dS m-1 as moderate salinity and 2.43 dS m-1 as elevated. For all variables analyzed, except for the relative chlorophyll index in beet plants, it was found that the increase in soil salinity resulted in significant development losses of beet and radish plants. Therefore, we concluded that beet and radish crops are sensitive to the variation in soil salinity, even in relatively low concentrations, making these species an unattractive choice for cultivation in systems that present this problem.